The determinants of corporate FX speculation – Why firms increase risk. Issue 5 (12th November 2021) - Hecht, Andreas
Abstract : Purpose: Empirical evidence on the determinants of corporate FX speculation is ambiguous. We note that the conflicting findings of prior studies could be the result of different methodologies in determining speculation. Using a novel approach to defining speculative activities, we seek to help solve the puzzle of the determinants of speculation and examine which firms engage in such activities and why they do so. Design/methodology/approach: This paper examines an unexplored regulatory environment that contains publicly reported FX risk data on the firms' exposures before and after hedging per year and currency. This unprecedented data granularity allows us to use actual reported volumes instead of proxy variables in defining speculation and to examine whether the convexity theories are empirically supported in FX risk management. Findings: We find that frequent speculators are smaller, have more growth opportunities and possess lower internal resources, which indicates unprecedented empirical evidence for the convexity theories in FX risk management. Further, we provide evidence that corporate speculation might be linked to the application of hedge accounting. Practical implications: We help solve the questions of which and why firms engage in speculative activities. This can provide valuable information to various stakeholders such as financial analysts, investors, or regulators, which can help prevent imperiling corporate losses and curb excessive speculative financial activities. Originality/value: In order to question the unresolved issue of the determinants of speculation, this paper is the first to use openly available accounting data with actual reported FX exposure information before and after hedging in defining speculation, instead of relying on proxy variables for FX exposure and derivative usage with potential estimation errors.